2022
DOI: 10.1530/ec-21-0412
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypovitaminosis D in pregnant refugees arriving in Europe: neonatal outcomes and importance of prenatal intervention

Abstract: Adequate vitamin D levels are particularly important in pregnant women for both the maternal and neonatal health. Prior studies have shown a significantly high prevalence of vitamin D deficiency (VDD) among refugees. However, no study has addressed the prevalence of VDD in pregnant refugees and its effects on neonatal health. In this study, we examined the prevalence of VDD in refugee pregnant women living in Greece and compared our results with Greek pregnant inhabitants. Vitamin D deficiency was frequent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A participant quotation reflecting this finding was: "The only time you would have a natural birth was if you came in and they didn't have time to get you to an operating room" [32]. However, Liori et al reported a lower rate of cesarean birth among refugees compared to Greek citizens [52]. Moreover, women received poor postnatal support [35,39,51].…”
Section: Objective 4: "Prevent Excess Maternal and Newborn Morbidity ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A participant quotation reflecting this finding was: "The only time you would have a natural birth was if you came in and they didn't have time to get you to an operating room" [32]. However, Liori et al reported a lower rate of cesarean birth among refugees compared to Greek citizens [52]. Moreover, women received poor postnatal support [35,39,51].…”
Section: Objective 4: "Prevent Excess Maternal and Newborn Morbidity ...mentioning
confidence: 99%
“…Moreover, women received poor postnatal support [35,39,51]. Maternal vitamin D deficiency (VDD) was significantly higher for refugees than for Greeks, which led to most of the refugee newborns being affected by VDD [52]. The quality of food was poor; pregnant and postpartum women did not get any specialized food [35,37], and it was generally difficult to access vitamins and minerals [51].…”
Section: Objective 4: "Prevent Excess Maternal and Newborn Morbidity ...mentioning
confidence: 99%